2020
DOI: 10.1002/adom.202001023
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Delayed Phosphorescence and Interchromophore Exciton Coupling in a Platinum‐Based Organometallic Emitter

Abstract: electrochemical properties of the constituent materials as well as intra-and intermolecular interactions. Molecular self-assembly in π-conjugated systems is essential because it opens up an avenue to organic materials with desired spectroscopic properties and electrochemical activities. [1] While organic π-conjugated structures have been considerably studied, the exploration of aggregates or gels containing metalorganic materials is relatively rare. [2] Platinum emitters produce long-lived and phosphorescent 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…In general, the enhanced photoactivity of hydrogenated TiO 2 can be ascribed to extra visible light absorption as well as to the optimized surface structures for reducing charge recombination and enhancing charge transfer. [131][132][133][134][135][136] By contrast, Mohajernia et al reported the annealing of TiO 2 in the Ar/H 2 atmosphere. 105 They found that the enhanced PEC performance should be dominantly attributed to strongly improved conductivity (i.e., semimetallic properties) as a result of the formation of O vac and Ti 3+ , and slightly due to the enhancement in light absorption.…”
Section: Post-annealing Treatmentsmentioning
confidence: 97%
“…In general, the enhanced photoactivity of hydrogenated TiO 2 can be ascribed to extra visible light absorption as well as to the optimized surface structures for reducing charge recombination and enhancing charge transfer. [131][132][133][134][135][136] By contrast, Mohajernia et al reported the annealing of TiO 2 in the Ar/H 2 atmosphere. 105 They found that the enhanced PEC performance should be dominantly attributed to strongly improved conductivity (i.e., semimetallic properties) as a result of the formation of O vac and Ti 3+ , and slightly due to the enhancement in light absorption.…”
Section: Post-annealing Treatmentsmentioning
confidence: 97%
“…Linear sweep voltammetry (LSV) at a potential range from À0.2 to 1 V vs. Ag/AgCl at a sweep rate of 10 mV s À1 was performed. [30][31][32] In a dark environment, consecutive cyclic voltametric (CV) measurements were conducted at a scan rate of 1 mV s À1 , with a potential window from À0.3 V to 0.5 V vs. Ag/AgCl. For an electrochemical kinetic study, a potential window from À1.1 V to 0.4 V vs. Ag/AgCl at different scan rates was used.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…[35][36][37] With regards to the composition of hybrid perovskites, Cl, Br, I, and/or metal elements can be used for element doping to optimize the properties of perovskites. [38][39][40][41][42] Chen et al 43 have doped Mn 2+ and Yb 3+ into the perovskite structure, which has been reported to help induce additional dopant-related emission bands, leading to dual emissions. [44][45][46] The halide doping strategy can be employed to tune the bandgap value of perovskites.…”
Section: Element Dopingmentioning
confidence: 99%